Подводные разведки в районе античных городищ Китей и Акра в 2009 г. - Воронов, С.А.; Бейлина, С.А.; Куликов, А.В. (Археологічні дослідження в Україні, 2010)
Joint expedition of the Department of Underwater Heritage of the IA NASU and the Crimean Branch of the IA NASU conducted the archaeological prospecting in waters of Ancient cities Cytae and Acra in the southern part of Strait of Kerch. Visual search in the coastal line up to 100 m wide was made, and series of underwater trenches was laid to specify the stratigraphy and to collect the dating materials.